(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In this article, we will talk briefly about mucormycosis (Black Fungus). Mucormycosis is a name that most doctors are acquainted with, and it refers to a collection of different mycoses caused by one of the several saprophytic fungi in the Mucorales order. Although the number of Mucorales species that cause human disease is small, case reports imply that, under the right circumstances, species of Mucorales that were previously thought to be harmless commensals could produce invasive disease. The fact that the names of the fungi have changed over time as more information about their taxonomy has been revealed has made identifying organisms recovered from human infections more difficult. To add to the confusion, mucormycosis has been given several other names, none of which are particularly helpful from a medical standpoint. Mucormycosis was referred to as phycomycosis while Phycomyces was part of the taxonomic lexicon. Mucorales-related disorders have also been given the label Zygomycosis. The name zygomycosis refers to the Zygomycetes class, which includes both Mucorales and Entomophthorales, which cause diseases that are fundamentally distinct from those caused by Mucorales. Furthermore, the name of mycotic diseases is not usually taken from the name of the causative fungus class. As a result, mucormycosis and entomophthoramycosis appear to be appropriate nomenclature for the two diseases caused by the Mucorales and Entomophthorales, respectively. The goal of this study is to go over the most up-to-date information on mucormycosis.